The Influence Of Online Credible Reviews With Brand Trust As An Intervening Variable On Purchase Intention ( A Study On Adorable Project In Bandung) - Shella Natasya Sri Mutiara Baringbing; Arianis Chan; Lina Auliana (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Amid Indonesia's e-commerce surge, online review credibility increasingly shapes purchase decisions on platforms like Shopee, yet fake reviews erode brand trust. This study examines the influence of online review credibility on purchase intention with brand trust as a mediating variable among Adorable Project consumers in Bandung. Employing a quantitative survey approach with cross-sectional design, data from 100 purposive-sampled Shopee buyers were analyzed using PLS-SEM via SmartPLS 4.0. Instruments adapted validated scales measuring source/review/consumer characteristics (Cheung et al., 2009), brand reliability/intentions (Delgado-Ballester et al., 2003), and multi-dimensional purchase intentions (Ferdinand, 2012). Results reveal significant direct effects: credibility → trust (β=0.775, p=0.000), trust → intention (β=0.526, p=0.006), credibility → intention (β=0.410, p=0.033), and indirect mediation (β=0.408, p=0.015), explaining 78% intention variance. In conclusion, brand trust partially mediates credible reviews' impact, urging local brands to prioritize authentic, photo-verified testimonials over incentives.